2018
DOI: 10.1177/1049732318756301
|View full text |Cite
|
Sign up to set email alerts
|

Integrating a Patient-Controlled Admission Program Into Mental Health Hospital Service: A Multicenter Grounded Theory Study

Abstract: Patient-controlled admissions (PCAs) enable mental health patients by means of a contract to initiate an admission at a mental health hospital unit without using traditional admission procedures. This study was part of a 3-year Danish multicenter project, and we explored how mental health professionals experienced and managed the implementation of a PCA program. The methodology was grounded theory and the sample included 26 participants. We performed a constant comparative analysis to explore the concerns, att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…With a retrospective explorative method such as interviews, participants may tend to be positive about their experiences. However, in a qualitative study of MHPs' perspectives, it was found that the staff also experienced that patients gained more responsibility (Ellegaard et al., 2018). A cross‐sectional study found that psychotic symptoms were determinants of quality of life for patients with schizophrenia and suggest providing interventions to train patients’ ability in self‐help and seeking help from others in order to promote skills of symptom management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With a retrospective explorative method such as interviews, participants may tend to be positive about their experiences. However, in a qualitative study of MHPs' perspectives, it was found that the staff also experienced that patients gained more responsibility (Ellegaard et al., 2018). A cross‐sectional study found that psychotic symptoms were determinants of quality of life for patients with schizophrenia and suggest providing interventions to train patients’ ability in self‐help and seeking help from others in order to promote skills of symptom management.…”
Section: Discussionmentioning
confidence: 99%
“…In Denmark, a national multicentre study was carried out over 3 years. The Danish study found that the mental health professionals (MHP) strived to integrate PCA into clinical practice and were motivated by the idea of establishing a partnership with patients (Ellegaard, Bliksted, Mehlsen, & Lomborg, 2018). A survey study evaluating this programme found that the patients signed a PCA contract to receive help early and that they initiated an admission to prevent symptoms increasing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrating user participation into current care models can be done in diverse ways and encounters different challenges depending on the situation. Ellegaard et al [ 38 ] thoroughly discussed the implementation process for patient participation for a patient-controlled admission programme. Here, it was concluded that staff juggled an interaction between managing their work duties and managing the new user-led care situation.…”
Section: Resultsmentioning
confidence: 99%
“…To further create feelings of support for user participation, projects aiming to strengthen user partnerships should not merely superficially claim to be a project of user partnership, but show ownership of the partnership component [ 35 ]. This can for example be achieved through a bottom up approach showing the interest from the users or staff [ 30 , 32 , 38 ] and through equality of information [ 24 , 26 28 , 30 , 33 , 35 ].…”
Section: Resultsmentioning
confidence: 99%